Spór o Granicę Zofii Nałkowskiej - Marzec, Lucyna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2019)
The study discusses the critical literary discourse that began to unfold, after the premiere of Zofia Nałkowska’s Granica [Boundary] (1935), among the most important literary journals and critics as well writers of interbellum Poland. The monograph begins with a broad-ranging commentary on the above and its debates through the kaleidoscope of literary life and its workings in that period, bringing to the fore ensuing interpretative questions facing its initial readers. The main theme of discussion at the time was the question of ethics, with the voices of criticism and those of polemics unveiling the galaxy of worldview tensions in the first half of the 20th century. The second part of the study constitutes a selection of the thirteen most important commentaries on Granica and a critical reflection on the part of Zofia Nałkowska together with a critical commentary.
The Polemic Over Zofia Nałkowska’s Granica